DEVELOPMENT OF ALGORITHMS FOR THE GEOSPATIAL ARRAY VISUALIZATION MODULE DATA IN XML FORMAT: Array - Zarytskyi, O.; Bulaienko, M. (Municipal economy of cities. Series: «Economy science», 2021)
The purpose of the article is development of the issue of increasing the efficiency of the automation and visu-alization procedure for creating documentation based on the use of XML-files, which, unlike existing ones, simpli-fies data exchange and presentation, which allows to automate document flow while maintaining accurate data description. Stationary or portable technical devices in which information is stored in XML files are usually used as visu-alization tools. Such files are used to exchange information between the decision maker, users and spatially dis-tributed systems and are called exchange. The XML format significantly minimizes the amount of memory on the media, in this format, any tags are created that are analogous to the fields in the table. The XML exchange file is also one of the tools for filling the cartographic basis of the urban cadastre and cadastres of other natural re-sources. The study improved the method of monitoring regional resources, based on the methodology of parallel cal-culations, which, in contrast to existing ones, can be used to process large amounts of spatially distributed infor-mation, which improves the monitoring system of regional resources in processing complex structured requests and too many spatial objects. Thus, the control, classification, coding and reliability of information with the re-production of missing data by verification, conversion and validation of archival or new spatially distributed in-formation. All developed models, methods and software and hardware for building regional resources monitoring have been brought to the level of engineering methods, algorithms and software tools for computer implementation. Methods and algorithms are implemented using Digitals, FastReport software and C # programming languages. The approbation of the developed technology is carried out on the example of separate parts of the Kharkiv city and the village of Kotlyary territories.